The bloody truth: Investigating nurse phlebotomy competencies at a private laboratory in Johannesburg, South Africa - Lizelle Crous; S.J. Armstrong (AOSIS, 2016)
Background: With the introduction of the phlebotomist technician-certification programme in South Africa, nurses' phlebotomy competence, an acquired skill during basic training, was questioned. Various studies indicate that the majority of errors occur during the collection phase, causing negative outcomes for the patient. Objective: Despite in-service training, samples were rejected and linked to the nurse phlebotomist's sample collection technique. The purpose of this study was to establish if nurses' phlebotomy techniques could be improved through a workplace-training programme in the attempt to improve the quality of the test results. Method: The methodology used was a quantitative, experimental, pilot intervention study, based on a one group pre-test - post-test design. Data was collected by means of peer video recordings of the nurses (n = 20) based at outpatient departments of the laboratory. Independent evaluators evaluated the recordings against criterion-based observational checklists. Results: Compliance to standards on the venepuncture procedure was identified during the pre-test, with an average score of 61.9%. The training programme, developed to address all deviations from the standards, proved to be effective as the post-test compliance score was 85%. Conclusion: The reason for improving nurses' phlebotomy skills is to ensure accurate results that will assist clinicians caring for their patients. The results suggest that knowledge and skills were acquired, however further investigations are needed for guidance in the standardisation of training programmes and at what intervals should these training programmes be presented.